Blended collaboration problem-based learning to improve critical thinking ability and complete learning of students on human heredity materials - Suparini (Journal on Biology and Instruction, 2022)
Based on the analysis at SMAN 36 in Biology learning, some students do have not optimal critical thinking skills and have not achieved minimum completeness. This can be seen in the lack of willingness to ask questions, involvement in opinion, and formulating problems does not reflect questions that use higher-order thinking. The study aims to determine the improvement of critical thinking skills and learning completeness of students in class XII MIPA 4 SMAN 36 Jakarta in human heredity. The method used is classroom action research which consists of two cycles through BCPBL. Learning is carried out with presentation discussions to explain the cases of each group which are prepared asynchronously. Data collecting by tests, observation of learning activities, and student response questionnaires. The research data were analyzed using a comparative description followed by reflection. The comparative description is done by comparing the initial condition data, cycles I and II, both for learning activities and learning outcomes. The results of this study indicate that BCPBL can improve critical thinking skills and complete learning from cycle I to cycle II. The results of the daily assessment in the first cycle showed that 28 students (77.78%) completed. The second cycle showed that 31 students (86.11%) completed it. Through BCPBL learning activities, students have an active learning experience, have interest, and respond as expected.